Theorizing the postcolonial city of Kuching : Colonial Logistics and Hybrid Spatialities in Kuching, Malaysia - Azmah, Arzmi; Julaihi, Wahid (Routledge, 2023)
The city plan of Kuching is not influenced by systematic planning principles, but rather, it is deeply embedded within colonial infrastructural logistics to meet the demands of global trade services and social structures. The postcolonial city is a palimpsest of hierarchical and territorial imprints from former colonial governance. Much of urban growth is concentrated around nodes, prioritized for resource collection and distribution. Therefore, this paper delineates how the current state and city governance recalibrate inherited infrastructures of economic development from the past, resulting in fragmented hybrid spaces of ethnic enclaves and economically marginalized groups in this northwest city of Borneo. We narrate how the Brooke dynasty, British administration and the Malaysian state have each developed and reappropriated logistics infrastructure based on their own agenda, leaving an indelible mark on the urban fabric and society of Kuching today. These findings are based on content analysis of city plans, visual surveys, government media, and secondary sources. We aim to open up new ways of understanding how multi-layered infrastructure and spaces produced by successive waves of different political strategies resulted in uneven development around the postcolonial city, and why some centres are given preference over others.